Altered Right Ventricular Mechanical Properties Are Afterload Dependent in a Rodent Model of Bronchopulmonary Dysplasia - Patel, Jitandrakumar R.; Barton, Gregory P.; Braun, Rudolf K.; Goss, Kara N.; Haraldsdottir, Kristin; Hopp, Alexandria; Diffee, Gary; Hacker, Timothy A.; Moss, Richard L.; Eldridge, Marlowe W. (Frontiers in Physiology, 2017)
Infants born premature are at increased risk for development of bronchopulmonary dysplasia (BPD), pulmonary hypertension (PH), and ultimately right ventricular (RV) dysfunction, which together carry a high risk of neonatal mortality. However, the role alveolar simplification and abnormal pulmonary microvascular development in BPD affects RV contractile properties is unknown. We used a rat model of BPD to examine the effect of hyperoxia-induced PH on RV contractile properties. We measured in vivo RV pressure as well as passive force, maximum Ca2+ activated force, calcium sensitivity of force (pCa50) and rate of force redevelopment (ktr) in right ventricular skinned trabeculae isolated from hearts of 21- and 35-day old rats pre-exposed to 21% oxygen (normoxia) or 85% oxygen (hyperoxia) for 14 days after birth. Systolic and diastolic RV pressure were significantly higher at day 21 in hyperoxia exposed rats compared to normoxia control rats, but normalized by 35 days of age. Passive force, maximum Ca2+ activated force, and calcium sensitivity of force were elevated and cross-bridge cycling kinetics depressed in 21-day old hyperoxic trabeculae, whereas no differences between normoxic and hyperoxic trabeculae were seen at 35 days. Myofibrillar protein analysis revealed that 21-day old hyperoxic trabeculae had increased levels of beta-myosin heavy chain (MHC), atrial myosin light chain 1 (aMLC1; often referred to as essential light chain), and slow skeletal troponin I (ssTnI) compared to age matched normoxic trabeculae. On the other hand, 35-day old normoxic and hyperoxic trabeculae expressed similar level of - and -MHC, ventricular MLC1 and predominantly cTnI. These results suggest that neonatal exposure to hyperoxia increases RV afterload and affect both the steady state and dynamic contractile properties of the RV, likely as a result of hyperoxia-induced expression of -MHC, delayed transition of slow skeletal TnI to cardiac TnI, and expression of atrial MLC1. These hyperoxia-induced changes in contractile properties are reversible and accompany the resolution of PH with further developmental age, underscoring the importance of reducing RV afterload to allow for normalization of RV function in both animal models and humans with BPD.